Temuri Queens Strengthening Diplomatic Relations (Zien Journal of Social Sciences and Humanities, 2023)
In the article, based on historical sources, the conclusions about the life path of Amir Temur and the women of the Timurid dynasty, especially the princesses, some of their activities on the political and social front, and their role in the development of diplomatic relations are presented.